Highly Adhesive Antibacterial Bioactive Composite Hydrogels With Controllable Flexibility and Swelling as Wound Dressing for Full-Thickness Skin Healing - Lan, Guanhua; Zhu, Suping; Chen, Dong; Zhang, Hua; Zou, Lijin; Zeng, Yuanlin (Frontiers in Bioengineering and Biotechnology, 2021)
Polyzwitterionic hydrogels as skin wound dressings have been extensively studied owing to their superior antibacterial properties and skin adhesiveness, but their practical applications still suffer from low adhesion strength and high swelling ratio, which hinder the application of hydrogel for cutaneous healing. Here, we developed a novel biocompatible poly(sulfobetaine methacrylate) (PolySBMA) composite hydrogel with high stretchability, low swelling, strong skin-adhesiveness and antibacterial effect for enhancing wound healing. Naturally rigid polymers including quaternized chitosan methacrylate (QCSMA) and gelatin methacrylate (GelMA) are used as bioactive crosslinkers to endow hydrogel with low swelling ratio and high bioactivity. The optimized hydrogel has excellent mechanical flexibility, with the ultimate tensile strength, tensile strain, modulus and toughness of up to 344.5 kPa, 364%, 14.7 kPa and 33.4 kJ·m-3, respectively. Adhesiveness of the hydrogel to the skin tissue is as high as 38.2 kPa, which is critical for stopping the bleeding from the wound. The synergistic contributions from the PolySBMA and QCSMA endow hydrogel with good antibacterial properties against both Gram-positive S. aureus and Gram-negative E. coli. Moreover, the natural polymer cross-linked polyzwitterionic hydrogel shows good cell activity, hemocompatibility, and histocompatibility. The in vivo full-thickness skin defect model demonstrates that the SQG hydrogel efficiently improves the granulation tissue formation and collagen deposition. In summary, such superiorly skin-adhesive antibacterial biocompatible hydrogel with controllable flexibility and swelling holds great promise as wound dressings for acute wounds.